Paradoxical impact of two folate receptors, FRα and RFC, in ovarian cancer: effect on cell proliferation, invasion and clinical outcome. - Michelle K Y Siu (Public Library of Science (PLoS), 2012)
Despite being an essential vitamin, folate has been implicated to enhance tumor growth, as evidenced by reports on overexpression of folate receptor alpha (FRα) in carcinomas. The role of another folate transporter, reduced folate carrier (RFC), is largely unknown. This study investigated the roles of folate, FRα and RFC in ovarian cancers. We demonstrated FRα mRNA and protein overexpression and reduced RFC expression in association with FRα gene amplification and RFC promoter hypermethylation, respectively. FRα overexpression was associated with tumor progression while RFC expression incurred a favorable clinical outcome. Such reciprocal expression pattern was also observed in ovarian cancer cell lines. Folate was shown to promote cancer cell proliferation, migration and invasion in vitro, and down-regulate E-cadherin expression. This effect was blocked after either stable knockdown of FRα or ectopic overexpression of RFC. This hitherto unreported phenomenon suggests that, RFC can serve as a balancing partner of FRα and confer a protective effect in patients with high FRα-expressing ovarian carcinomas, as evidenced by their prolonged overall and disease-free survivals. In conclusion, we report on the paradoxical impact of FRα (putative oncogenic) and RFC (putative tumor suppressive) in human malignancies. FRα and RFC may potentially be explored as therapeutic target or prognostic marker respectively. We recommend caution and additional research on folate supplements in cancer patients.